Beyond cDC1: Emerging Roles of DC Crosstalk in Cancer Immunity - Noubade, Rajkumar; Majri-Morrison, Sonia; Tarbell, Kristin V. (Frontiers in Immunology, 2019)
Dendritic cells (DCs) efficiently process and present antigens to T cells, and by integrating environmental signals, link innate and adaptive immunity. DCs also control the balance between tolerance and immunity, and are required for T-cell mediated anti-tumor immunity. One subset of classical DCs, cDC1, are particularly important for eliciting CD8 T cells that can kill tumor cells. cDC1s are superior in antigen cross-presentation, a process of presenting exogenous antigens on MHC class I to activate CD8+ T cells. Tumor-associated cDC1s can transport tumor antigen to the draining lymph node and cross-present tumor antigens, resulting in priming and activation of cytotoxic T cells. Although cross-presenting cDC1s are critical for eliciting anti-tumor T cell responses, the role and importance of other DC subsets in anti-tumor immunity is not as well characterized. Recent literature in other contexts suggests that critical crosstalk between DC subsets can significantly alter biological outcomes, and these DC interactions likely also contribute significantly to tumor-specific immune responses. Therefore, antigen presentation by cDC1s may be necessary but not sufficient for maximal immune responses against cancer. Here, we discuss recent advances in the understanding of DC subset interactions to maximize anti-tumor immunity, and propose that such interactions should be considered for the development of better DC-targeted immunotherapies.